The Synergistic Effect of Exogenous Glutamine and Rifampicin Against Mycobacterium Persisters - Huang, Xue; Duan, Xiangke; Li, Jiang; Niu, Jingjing; Yuan, Siqi; Wang, Xiaoyu; Lambert, Nzungize; Li, Xue; Xu, Junqi; Gong, Zhen; Yan, Shuangquan; Xie, Longxiang; et al. (Frontiers in Microbiology, 2018)
Abstract Persisters, stochastic dormant variants of normal bacteria cell, represent a significant portion of the survivors upon exposure to antibiotics and other environmental stresses, which contributes substantially to high level antibiotics tolerance. Glutamine is a crucial component of the Mycobacteria nitrogen pool that is indispensable for survival upon stresses. To study whether a synergistic effect exiits between glutamine and antibiotics against Mycobacterial persisters, the efficacy of rifampicin alone or together with exogenous glutamine upon M. smegmatis mc2 155 persisters was monitored. The result showed that glutamine decreases M. smegmatis tolerance to rifampicin upon starvation. The reactive oxygen species level of the strains treated with rifampicin and glutamine increased. The synergism of glutamine and rifampicin to kill persisters might derive from altering the oxidative phosphorylation and TCA cycle, as both evidenced by both ATP level increase and transcriptome change. Glutamine might represent a synergistic agent of rifampicin to kill Mycobacteria persisters.